2002
DOI: 10.1097/00000658-200209000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Pretransplant Model to Predict Posttransplant Survival in Liver Transplant Patients

Abstract: ObjectiveTo develop a prognostic model that determines patient survival outcomes after orthotopic liver transplantation (OLT) using readily available pretransplant variables. Summary Background DataThe current liver organ allocation system strongly favors organ distribution to critically ill recipients who exhibit poor survival outcomes following OLT. A severely limited organ resource, increasing waiting list deaths, and rising numbers of critically ill recipients mandate an organ allocation system that balanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
138
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(149 citation statements)
references
References 29 publications
8
138
3
Order By: Relevance
“…In the absence of firm guidelines, this is likely to be interpreted as discriminatory by the lay public or outside observers. Many models and methods of risk assessment have been described to identify patients most likely to benefit from re-LT. 13,19,20 These models have shown that patient preoperative ventilatory status, serum creatinine level, and bilirubin level are among the major determinants of postoperative survival. A model described by Rosen et al 19 identified age, bilirubin level, creatinine level, UNOS status, and cause of graft failure as independent predictors of post-re-LT survival.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of firm guidelines, this is likely to be interpreted as discriminatory by the lay public or outside observers. Many models and methods of risk assessment have been described to identify patients most likely to benefit from re-LT. 13,19,20 These models have shown that patient preoperative ventilatory status, serum creatinine level, and bilirubin level are among the major determinants of postoperative survival. A model described by Rosen et al 19 identified age, bilirubin level, creatinine level, UNOS status, and cause of graft failure as independent predictors of post-re-LT survival.…”
Section: Discussionmentioning
confidence: 99%
“…Another model identified donor and recipient age, creatinine level, bilirubin level, and warm and cold ischemia times as independent variables affecting survival. 20 Azoulay et al 2 found urgency of transplantation, age, and creatinine level to be independent variables affecting survival after re-LT. We perhaps could add HCV infection and transplantation for PGNF to the list of poor predictors of survival after re-LT.…”
Section: Discussionmentioning
confidence: 99%
“…Prognostic models have been developed recently, but these studies predate the Model for End-Stage Liver Disease (MELD) scoring system, which incorporates many of these factors. [24][25][26] In the era of MELD scoring, one can speculate that patients undergoing OLT are sicker and have more risk factors for poor outcome than those who underwent OLT under the UNOS status scoring system.Considerable concern and debate surround the topic of re-OLT in general and specifically in HCV-infected patients. Aims of the study are to determine the current prevalence of HCV-related liver disease in the re-OLT population, survival after re-OLT for patients with HCV versus other diseases, and whether pre-OLT MELD scores are predictive of survival outcome.…”
mentioning
confidence: 99%
“…Prognostic models have been developed recently, but these studies predate the Model for End-Stage Liver Disease (MELD) scoring system, which incorporates many of these factors. [24][25][26] In the era of MELD scoring, one can speculate that patients undergoing OLT are sicker and have more risk factors for poor outcome than those who underwent OLT under the UNOS status scoring system.…”
mentioning
confidence: 99%
“…Two groups, UCLA (24) and University of Pennsylvania (25), presented data which challenged the potential utility of this system, and suggested that the MELD score may actually predict postoperative mortality. The merits of this MELD and PELD will undoubtedly be the focus of future analysis pending the accumulation of data in the first few years of this new allocation scheme.…”
Section: Organ Allocationmentioning
confidence: 99%